Quality of Service with the Satisfaction of Visitors to Breezy Hamlet - Gloria Meydelina; Irma Febryani; Tanti Tanti; Sutarto Wijono; Valensia Putri (International Journal Labs, 2023)
Service quality can affect customer satisfaction, and customer satisfaction is determined by service quality. Dusun Semilir is one of the tourist destinations in Central Java which is visited by many tourists. As a tourism facility that offers the beauty and charm of community resources, it is important to know the level of customer satisfaction that directly perceives the brand image of a tourist destination and tourism service provider. Therefore the purpose of this study was to identify the relationship between service quality and visitor satisfaction in Dusun Semilir. The hypothesis is answered by using Spearman's correlation. The survey method is target sampling (sampling method) based on the criteria requested by the researcher, and sampling is carried out using brochures or pamphlets distributed on various social media.